Advantages of Friction Welding of Fittings with Small Diameter Conical Contact Form - Yu. V. Poletaev; V. V. Shchepkin (Advanced Engineering Research, 2023)
Introduction. As numerous production tests show, the use of manual arc welding (MAW) of thick-walled fittings of small diameter (up to 80 mm) does not provide a high-quality weld joint that meets the requirements of regulatory and technical documents of nuclear power plants (NPP). The solution to this problem is possible on the basis of research and development of welding technology with optimal heat input instead of MAW. Existing fusion welding technologies do not allow for optimal regulated heat input. However, this can be realized during the development and further use of the friction welding (FW) method. Therefore, this work aimed at developing a technology based on an automated technique of friction welding, which could provide the enhancing of the quality of weld joints of small diameter fittings of power equipment to the level of regulatory requirements.Materials and Methods. Small diameter fittings with a conical contact surface made of low-alloy steel 10GN2MFA were used. The experimental study was performed on a friction welding machine MST–41. Methods of non-destructive and destructive quality control were used in accordance with the regulatory and technical documentation of nuclear power engineering.Results. A methodology was developed, and the optimal dimensions of the conical contacting surface under welding were determined. It was shown that optimal heat input during friction welding was achieved by preparing a conical contacting surface in the angle range α = 30º–40º.  The methodology and parameters of the friction welding mode for models of small diameter fittings were experimentally tested. In the course of the research, a cyclogram of the friction welding process was obtained and described, which confirmed the stage-by-stage formation of the weld joint due to the sequential inclusion of annular sections of the conical surface of the connected parts in the heating stage. The results of non-destructive and destructive testing were obtained, confirming the presence of a high-quality weld joint at the level of the requirements of the regulatory and technical documents of the NPP.Discussion and Conclusion. The obtained research results can be used to develop the technology of friction welding of pipes, as well as products made of carbon and low-alloy steels.